Phospho-N-Acetyl-Muramyl-Pentapeptide Translocase from Escherichia coli: Catalytic Role of Conserved Aspartic Acid Residues - Lloyd, Adrian J. (American Society for Microbiology, 2004)
Phospho-N-acetyl-muramyl-pentapeptide translocase (translocase 1) catalyzes the first of a sequence of lipid-linked steps that ultimately assemble the peptidoglycan layer of the bacterial cell wall. This essential enzyme is the target of several natural product antibiotics and has recently been the focus of antimicrobial drug discovery programs. The catalytic mechanism of translocase 1 is believed to proceed via a covalent intermediate formed between phospho-N-acetyl-muramyl-pentapeptide and a nucleophilic amino acid residue. Amino acid sequence alignments of the translocase 1 family and members of the related transmembrane phosphosugar transferase superfamily revealed only three conserved residues that possess nucleophilic side chains: the aspartic acid residues D115, D116, and D267. Here we report the expression and partial purification of Escherichia coli translocase 1 as a C-terminal hexahistidine (C-His(6)) fusion protein. Three enzymes with the site-directed mutations D115N, D116N, and D267N were constructed, expressed, and purified as C-His(6) fusions. Enzymatic analysis established that all three mutations eliminated translocase 1 activity, and this finding verified the essential role of these residues. By analogy with the structural environment of the double aspartate motif found in prenyl transferases, we propose a model whereby D115 and D116 chelate a magnesium ion that coordinates with the pyrophosphate bridge of the UDP-N-acetyl-muramyl-pentapeptide substrate and in which D267 therefore fulfills the role of the translocase 1 active-site nucleophile.